BIOTECHNOLOGY MODULE FOR SPACE BIOLOGICAL LIFE SUPPORT SYSTEMS : BIOTECHNOLOGY MODULE FOR SPACE BIOLOGICAL LIFE SUPPORT SYSTEMS - Gramatikov, Pavlin; Totorov, Raycho; Hotinov, Boris; Karadjov, Julian (JOURNAL SCIENTIFIC AND APPLIED RESEARCH, 2023)
For the cultivation of microorganisms light, feeding with carbon dioxide, minerals, stable temperature and pH of the environment are provided. Designs for closed circulating photobioreactors for algae Chlorella vulgaris are described for the purpose of their use in space. The main stages of different production for Chlorella vulgaris (strain ИФР № С- 111) are presented. A microprocessor controlled module is proposed for terrestrial experiments.